2016
DOI: 10.1007/978-3-319-40764-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cells and Integrity of the Nervous System

Abstract: Today, there is enormous progress in understanding the function of glial cells, including astroglia, oligodendroglia, Schwann cells, and microglia. Around 150 years ago, glia were viewed as a glue among neurons. During the course of the twentieth century, microglia were discovered and neuroscientists' views evolved toward considering glia only as auxiliary cells of neurons. However, over the last two to three decades, glial cells' importance has been reconsidered because of the evidence on their involvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 159 publications
2
40
0
Order By: Relevance
“…Moreover, for the first time the dye uptake method was used in the brain injury model of in vitro to prove the occurrence of pyroptosis. The results showed that HT22 cells developed cell pyroptosis earlier than BV2 cells, which may help explain the cell type-specific susceptibility in vivo because neurons are more vulnerable to ischemia-induced injury than microglia 11 [30][31][32]. In our study, we also found no changes in GSDME activation in both neuronal cells and microglia after OGD/R.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, for the first time the dye uptake method was used in the brain injury model of in vitro to prove the occurrence of pyroptosis. The results showed that HT22 cells developed cell pyroptosis earlier than BV2 cells, which may help explain the cell type-specific susceptibility in vivo because neurons are more vulnerable to ischemia-induced injury than microglia 11 [30][31][32]. In our study, we also found no changes in GSDME activation in both neuronal cells and microglia after OGD/R.…”
Section: Discussionsupporting
confidence: 47%
“…as well as elevated seizure outcomes observed in people with epilepsy ( 4 ). A previous study demonstrated that microglial cells in epileptic rats feature widespread, activation-associated morphological changes such as increase in cell number density, massive up-regulation of CD11b and de-ramification ( 14 ). In gliomas, microglia and macrophages represent a significant component of the inflammatory response, and the balance of pro- and anti-inflammatory functions of them dictates their antitumor activity ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glia serve a pivotal role in the initiation and maintenance of the CNS immune response, and it involves in defining central nervous system architecture, brain metabolism, and the survival of neurons, development and modulation of synaptic transmission, propagation of nerve impulses, and many other physiological functions ( 13 ). In the recently years, the contribution of glial cells, mainly astrocytes and microglia, to the pathophysiology of epilepsy is increasingly appreciated ( 11 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The neuron-glia interactions are crucial for normal functioning of the brain during development and throughout adult life. The emerging line of evidence has shed light on the importance of glia in their bidirectional communication with neurons, their adaptability in various pathologies, modulation of neuronal activity, and phenotypic changes in response to neuronal injury (Benarroch, 2005;von Bernhardi et al, 2016). Throughout the brain tissue, neurons are closely associated with glial cells including astrocytes, oligodendrocytes, and microglia and their dynamic interactions are important for normal brain function (Chung et al, 2015;Meyer and Kaspar, 2017).…”
Section: Introductionmentioning
confidence: 99%